Measuring fracture resistance behaviour of tungsten using chevron-notched micro-cantilevers - Li, B (2017)
The fracture properties of tungsten-tantalum alloy (W-1%Ta), one of the candidate material for the plasma facing components in proposed fusion reactor design, were investigated using microscale chevron-notched cantilever bending tests at both ambient and high temperature (700 °C) conditions. Finite element analysis (FEA) were used to optimise the crack stability of the chevron notch design and obtain the geometry-dependent stress-intensity factors (SIFs) and stiffness vs. crack length relationships. Room temperature chevron-notched micro-cantilevers of single-crystal silicon were used to validate the FE-calculated SIFs. The average fracture toughness (KIc) measured from Si cantilevers was 0.85±0.04 MPa·m0.5 , which was in good agreement with previously reported macroscopic values (0.7~1 MPa·m0.5 ). This result showed no size-effect in fracture toughness of the intrinsically brittle silicon, and chevron-notched micro-cantilever was an effective micro-specimen geometry for measuring fracture toughness. Stable crack growth (SCG) accompanied with plastic deformation were observed in most room temperature tested chevron-notched W-1%Ta micro-cantilevers. Linear-elastic fracture mechanical analysis (LEFM) previously used for the brittle Si cantilevers will underestimate the true fracture toughness of the semi-brittle W-1%Ta, hence an elastic-plastic fracture mechanical analysis (EPFM) was employed to measure the fracture toughness using the fracture resistance curve (J-R curve) approach. The average EPFM-calculated fracture toughness at crack instability (KQc) was 25.8±2.3 MPa·m0.5 , whereas the average LEFM-calculated fracture toughness was 4.3±0.2 MPa·m0.5 . The EPFM-calculated microscopic KQc were significantly higher than previously reported macroscopic value, possibly due to the larger crack tip plastic zone to specimen size ratio. Using Irwin’s estimation, the crack tip plastic zone radius of W-1%Ta micro-cantilevers ranged from 200~1500 nm, which were significantly larger than the crack tip plastic zone radius of the intrinsically brittle silicon (~5 nm), suggesting the size effect seen in fracture toughness might arise from the larger plastic zone to specimen size ratio. Chevron-notched W-1%Ta micro-cantilevers up to 700 °C were tested using a high- temperature nanoindenter (Micro Materials® NanoTest Xtreme). Prior testing, the temperature of the indenter and sample were carefully matched to minimise the thermal drift effects. The EPFM-calculated KQc increased gradually with temperature, until a sharp increase (40.5±3.2 MPa·m0.5) was observed at 700 °C. This microscopic brittle-to-ductile transition temperature (BDTT) was significantly higher than the macroscopic BDTT (700 vs. 200 °C), possibly due to the higher strain rate used and the tantalum addition. The amount of SCG also increased with temperature, ranging from 500 nm at RT to 800 nm at 700 °C. The larger microscopic KQc (compared to macroscopic KIc in the same temperature regime) and SCG were probably caused by the combination of the extended crack tip plastic zone and extensive dislocation shielding effects, due to the thermally-activated dislocation activities. This thesis has demonstrated micro-fracture tests using chevron-notched cantilevers are capable of measuring the fracture resistance curves from the semi-brittle W-1%Ta. Due to larger crack tip plastic zone to specimen size ratio, the EPFM-calculated KQc were significantly higher than macroscopic values. A specimen size effect to fracture toughness is suggested, which should be carefully considered when performing micro-fracture testing of ductile materials.